Computational Biomechanics for Medicine Measurements, Models, and Predictions - Nielsen, Poul M. F.; Wittek, Adam.; Miller, Karol; Doyle, Barry; Joldes, Grand R.; Nash, Martyn P.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume comprises the latest developments in both fundamental science and patient-specific applications, discussing topics such as: cellular mechanics, injury biomechanics, biomechanics of the heart and vascular system, algorithms of computational biomechanics for medical image analysis, and both patient-specific fluid dynamics and solid mechanics simulations. With contributions from researchers world-wide, Computational Biomechanics for Medicine: Measurments, Models, and Predictions provides an opportunity for specialists in the field to present their latest methodologies and advancements.
Chapter1: Making head and neck reconstruction surgery an engineering process -- Chapter2: Atlas of Acceleration-Induced Brain Deformation from Measurements in Vivo -- Chapter3: Reconstruction of Real-World Car-to-Pedestrian Accident Using Computational Biomechanics Model: Effects of the Choice of Boundary Conditions of the Brain on Brain Injury Risk -- Chapter4: Computational Modeling of Fluid-Structure Interaction between Blood Flow and Mitral Valve -- Chapter5: Maximum Principal AAA Wall Stress is Proportional to Wall Thickness -- Chapter6: An Immersed Boundary Method for Detail-Preserving Soft Tissue Simulation from Medical Images -- Chapter7: A Flux-Conservative Finite Difference scheme for the numerical solution of the nonlinear bioheat equation -- Chapter8: Quantifying Carotid Pulse Waveforms Using Subpixel Image Registration -- Chapter9: A Discrete Element Method for modelling cell mechanics - application to the simulation of chondrocyte behavior in the growth plate -- Chapter10: Image-based biomechanical modelling of heart failure -- Chapter11: A comparison of biomechanical models for MRI to digital breast tomosynthesis 3D registration -- Chapter12: Towards a real-time full-field stereoscopic imaging system for tracking lung surface deformation under pressure controlled ventilation -- Chapter13: Patient-specific simulation: non-destructive identification method for soft tissue under large strain - Application to pelvic system -- Chapter14: Simulating Platelet Transport in Type-B Aortic Dissection.
Keywords: Biomedical engineering; Mathematics -- Data processing; Mechanics, Applied; Radiology; Medical physics; Control engineering; Robotics; Automation; Biomedical Engineering and Bioengineering; Computational Science and Engineering; Engineering Mechanics; Radiology; Medical Physics; Control, Robotics, Automation